MitoStores: chaperone‐controlled protein granules store mitochondrial precursors in the cytosol. (27th January 2023) - Krämer, Lena; Dalheimer, Niko; Räschle, Markus; Storchová, Zuzana; Pielage, Jan; Boos, Felix; Herrmann, Johannes M
Abstract: Hundreds of nucleus‐encoded mitochondrial precursor proteins are synthesized in the cytosol and imported into mitochondria in a post‐translational manner. However, the early processes associated with mitochondrial protein targeting remain poorly understood. Here, we show that in Saccharomyces cerevisiae, the cytosol has the capacity to transiently store mitochondrial matrix‐destined precursors in dedicated deposits that we termed MitoStores. Competitive inhibition of mitochondrial protein import via clogging of import sites greatly enhances the formation of MitoStores, but they also form during physiological cell growth on nonfermentable carbon sources. MitoStores are enriched for a specific subset of nucleus‐encoded mitochondrial proteins, in particular those containing N‐terminal mitochondrial targeting sequences. Our results suggest that MitoStore formation suppresses the toxic potential of aberrantly accumulating mitochondrial precursor proteins and is controlled by the heat shock proteins Hsp42 and Hsp104. Thus, the cytosolic protein quality control system plays an active role during the early stages of mitochondrial protein targeting through the coordinated and localized sequestration of mitochondrial precursor proteins. Synopsis: Nucleus‐encoded mitochondrial precursor proteins are synthesized in the cytosol and post‐translationally imported into mitochondria. Here, specific granules in the yeast cytosol—MitoStores—are found to serve as a transient buffer system when the synthesis of precursors exceeds the capacity of the mitochondrial import machinery. Mitochondrial precursor proteins can be transiently stored in the cytosol Precursors are sequestered in dedicated granules ("MitoStores") The chaperones Hsp42 and Hsp104 control MitoStore formation MitoStore formation prevents the cytotoxic effects of cytosolic precursors Abstract : Transient storage in newly identified cytosolic granules protects yeast cells from the toxic effects of excess mitochondrial matrix‐destined precursors.